Analysis of the Implementation of Physical Education Learning in the Independent Curriculum - Oman Unju Subandi; Fahmy Fachrezzy; Sujarwo Sujarwo; Abdul Halim (UNIB Press, 2024)
The essence of independent learning is the readiness and courage of teachers and students in the learning process. The aim of this research is to determine empirically the results of implementing the independent learning curriculum in PJOK learning in an integrated Islamic basic education unit in the city of Depok, West Java. The research method used was a qualitative approach through interviews, FGDs and questionnaires for 6 months (May-October 2023). The research results found: 44% of respondents were not ready to understand the independent curriculum yet, 46.9% of respondents were not ready for the independent curriculum in PJOK subjects, 47% were ready to implement the independent PJOK curriculum, 78% had implemented the independent PJOK curriculum. Thus, it was concluded that the readiness and implementation of the independent PJOK curriculum had been carried out well by the PJOK teachers at SDIT Depok City so that learning could proceed with the expectations and goals that had been set. The implication of this research is that the success of PJOK learning is supported by the teacher's readiness and understanding of the independent curriculum.